The associations between social support and mental health among Chinese immigrant pregnant and parenting women - Grace Tian; Natalia M. Rojas; Jennifer M. Norton; R. Gabriela Barajas-Gonzalez; Jacqueline Montesdeoca; Bonnie D. Kerker (BMC, 2024)
Abstract Background While it is recognized that social support can alleviate mental health symptoms, this relationship is not well-understood among Chinese pregnant and parenting immigrants in the United States. This study aims to bridge this gap by exploring the relationships between different types of social support and women's anxiety and depression, and examining how these associations vary with pregnancy status. Methods Data were obtained from a cross-sectional survey conducted in Simplified Chinese or Mandarin between March-June 2021 among 526 women who were pregnant and/or parenting a child under five years. The Patient-Reported Outcomes Measurement Information System (PROMIS) Anxiety, Depression, and Social Support scales were used to measure anxiety, depression, and social support levels. Descriptive statistics, t-tests, chi-square tests, and Pearson's correlations were employed for analysis. Hierarchical regression was conducted to investigate the main and interaction effects of social support types and pregnancy status on mental health outcomes. Results Compared to non-pregnant women, pregnant women reported higher mean scores for anxiety (non-pregnant: 55, pregnant: 59, p < 0.01) and depression (non-pregnant: 54, pregnant: 56, p = 0.02). Instrumental support displayed a significant main effect in relation to anxiety (β=-0.13, p = 0.01) and depression (β=-0.16, p < 0.01); emotional support exhibited a significant main effect solely on depression (β=-0.13, p = 0.01). Notably, the interaction effects between pregnancy status and both instrumental (β=-0.28, p = 0.01) and emotional support (β=-0.42, p < 0.01) were significant for anxiety. In contrast, informational support did not exhibit a significant impact on either anxiety or depression. Conclusions The findings indicate that tailoring support to the cultural context is crucial, especially for pregnant women in this Chinese immigrant community, with instrumental and emotional support being particularly beneficial in mitigating maternal anxiety.